The Effect of Blood Transfusion on Hemoglobin, Hematocrit, and Ferritin Levels in Children with Thalassemia at RSUDZA Banda Aceh - Telambanua, Arniat Christiani; Desi Maryasari (International Journal of Midwifery and Health Sciences, 2024)
In children with thalassemia, lower hemoglobin levels are associated with several symptoms of general weakness and decreased mental alertness that can cause disturbances in several quality-of-life domains. This study aimed to determine the effect of blood transfusion on hemoglobin levels, hematocrit, and ferritin levels in children with thalassemia at RSUDZA Banda Aceh. This type of research is a Quasy Experiment design one only group pretest and posttest. This research was conducted in July 2024. The population in this study was 59 pediatric patients with thalassemia while sampling used a simple random sampling technique of 30 respondents. Data were analyzed univariately and bivariately using the Paired sample t-test. The results of the study obtained an average hemoglobin level before blood transfusion of 6,350 gr / dL and after 11.44 gr / dL, an average hematocrit level before blood transfusion of 22.50% and after 40.23%, an average ferritin level before blood transfusion of 379.167 µg / L after 35.5475 µg / L. There is an effect of blood transfusion on hemoglobin levels (p = 0.000), hematocrit levels (p = 0.000), and ferritin levels (p = 0.000) in children with thalassemia at RSUDZA Banda Aceh. Based on the results, it can be concluded that blood transfusion affects hemoglobin levels, hematocrit, and ferritin levels in children with thalassemia. Suggestion: It is hoped that all health workers can provide information about the occurrence of thalassemia and it is hoped that they can provide information related to differences in hemoglobin, hematocrit, and ferritin levels in children with thalassemia.